The exploration classical music contribution to improve children's memory abilities - Zadrian Ardi; Siti Azizi Fauziyyah (Educational Guidance and Counseling Development Journal, 2018)
Memory is a part of the brain that will be used until the old later. Today a great many children who have low memory. However, it is not a possibility many ways to develop your child's memory. Even the music was also influential in the power of memory. However, not all types of music can have a great impact against the child's memory. There are some kids who don't like the music even while being given or learn something. Therefore, this paper will discuss on the influence of music in improving memory or memory. Especially the kind of classical music. Some studies experts suggest that classical music is indeed influential in increasing memory. Because classical music has a quiet and relaxed tones that mostly used to study because it can lower the stress level when working as a matter of practice. In this case, the memory and the music are a collaboration that fit when working on the problem. Because it can improve memory and decrease stress.